Penyuluhan Kesehatan Lingkungan - Suaib Suaib (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Environmental health is a science that studies the dynamics of interactive relationships between population groups or communities and all kinds of changes in environmental components such as various species of life, materials, substances, or forces around humans, which pose a threat, or have the potential to disrupt public health, and how to find preventive measures. The purpose of community service activities is to implement environmental health for the community so that the community can live clean and healthy in households/families, namely; family members' health improves and they are not easily sick, family members' productivity increases, and children grow up healthy and intelligent. The results of the community service activities entitled Environmental Health Counseling at Antang Village, Ujung Bori Makassar Posyandu have been carried out smoothly. The community's response was very good and they hoped that this community service activity could be carried out routinely.